Evaluation of process performance and microbial profile of household food waste anaerobic digestion - Khairuddin, Nuruljannah (2018)
Interest in household food waste treatment has increased in recent years due to the growing rate of its generation. In spite of the renewed attention on anaerobic digestion of household food waste, process stability is always becoming a concern among the practitioners. Moreover, anaerobic digestion performance at steadystate and the comprehensive characterizations of microbial community from wet to dry technologies were not compared in parallel. The main focus of this research work was to evaluate the process performance and microbial profile on household food waste anaerobic digestion. Biochemical methane potential (BMP) assays was conducted to access the suitability and feasibility of the substrate with different total solid (TS) content in 1 L reactor. The reactor were labelled as BMP.5 (5% TS), BMP.10 (10% TS) and BMP.15 (15% TS). Batch and semi-continuous experiments were conducted to evaluate and compare their process performance with TS content ranged 5 – 15%. Batch reactor (200 L) were labelled as B.5, B.10 and B.15 and semi-continuous reactor (10 L) were labelled as C.5, C.10 and C.15 for TS 5%, 10% and 15%, respectively. Co-digestion (1 L) was carried out to improve batch system with higher total solid contents (20 – 25% TS). All reactors configuration utilized in this study is employed in triplicate. Finally, microbial study utilizing Illumina next generation sequencing on steady-state of each anaerobic reactor was conducted. BMP.15 obtained the highest methane (CH4) yield (409 mL CH4/g VS) and mass reduction (75.4 – 78.3%). Better performance on volatile solid reduction (85.6%) and soluble chemical oxygen demand removal (77%) was seen in C.15. Higher methane production (425 mL CH4/g VS) was obtained from B.15. Approximately 3-folds increase in TS contents from 5 – 15%, the average of volatile solid (VS) reduction increased 2-folds (from 33% to 63%) for batch reactor while semi-continuous reactor reached 80 – 86% of reduction. The average methane yield increased 4-folds (240.4 – 425.0 mL CH4/g VS) in batch reactor and 1.8-folds (269.5 – 347.8 mL CH4/g VS) in semi-continuous reactor (ρ <0.05). In co-digestion experiments higher TS content from 20% to 25% were evaluated. The results revealed that by increasing TS concentration, the methane production improved 1.5-fold from mono-digestion. Highest methane production (475 mL CH4/g VS) was obtained in co-digestion reactor with 25% TS. Co-digestion had synergistic effect on methane production with the highest level of synergy (α = 1.61 – 2.14). Illumina MiSeq data showed significant shift of bacterial communities and that the phyla included Bacteroidetes, Firmicutes, Synergistetes and Chloroflexi. The relative abundance of phylum Bacteroidetes increased while Chloroflexi decreased at increasing TS content from 5% to 25%. Methanosarcina were abundant and dominant during the steady-state of anaerobic digestion at higher solid content in the reactor. Methanomicrobiales were mostly dominant in reactor working with lower solid content. In summary, a higher cumulative methane yield and better performances in terms of solid and mass organic reduction were achieved at higher TS content of AD. These findings also revealed the influenced of TS contents (ρ <0.01) on the behavior of the microbial community involved in anaerobic digestion of household food waste.